Server Performance Analysis Against Distributed Denial of Service (DDoS) Attacks (Case Study: Mataram University Academic Information System) - Rafli Gunawan Hadi; Ahmad Zafrullah Mardiansyah; Raphael Bianco Huwae (Journal of Computer Science and Informatics Engineering (J-Cosine), 2024)
Information technology advancement has significantly impacted Indonesia's education sector, including the University of Mataram. The university relies on the Sistem Informasi Akademik (SIA) for various academic activities. However, increasing users has led to challenges such as excessive traffic and server downtime. This research analyzes the impact of DDoS attacks on the SIA server's performance and utilizes Zabbix for server monitoring. The results show that DDoS attacks mainly burden the network traffic component, with a significant increase compared to normal conditions. CPU and RAM resources also increased but less significantly. Monitoring with Zabbix improves the efficiency of performance management, enabling real-time monitoring and easy-to-understand visualization. The findings help administrators identify the need to increase server capacity and implement DDoS detection and mitigation systems to maintain the quality and availability of academic services.